2016
DOI: 10.1038/srep30142
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis for hydroxy-L-proline-induced calcium oxalate nephrolithiasis in rats based on ultra-high performance liquid chromatography quadrupole time-of-flight mass spectrometry

Abstract: About 80% of kidney stones are composed of calcium oxalate (CaOx) with variable amounts of calcium phosphate, and hyperoxaluria is considered as an important factor of CaOx nephrolithiasis. However, the underlying metabolic mechanisms of CaOx nephrolithiasis remain undefined. In this study, we successfully developed a rat model with hydroxy-L-proline (HLP) -induced CaOx nephrolithiasis. Rats were continuously orally administrated with HLP for 28 days. Urine and blood samples were collected from the rats treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…In this context, altered urinary levels in stone formers may be suggestive of altered glycine metabolism that could lead to increased oxalate production and stone formation [ 35 ]. Our findings are in agreement with literature data [ 35 – 39 ], in which a decrease in the concentration of amino acids, including alanine, tryptophan, and threonine, was suggested to exert a possible inhibitory activity of crystalline aggregation [ 38 , 39 ]. Moreover, renal oxidative vulnerability due to changes in mitochondrial-glutathione and energy homeostasis was described in a rat model of calcium oxalate urolithiasis [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…In this context, altered urinary levels in stone formers may be suggestive of altered glycine metabolism that could lead to increased oxalate production and stone formation [ 35 ]. Our findings are in agreement with literature data [ 35 – 39 ], in which a decrease in the concentration of amino acids, including alanine, tryptophan, and threonine, was suggested to exert a possible inhibitory activity of crystalline aggregation [ 38 , 39 ]. Moreover, renal oxidative vulnerability due to changes in mitochondrial-glutathione and energy homeostasis was described in a rat model of calcium oxalate urolithiasis [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…To overcome the potential glyoxalate side effects to damage the kidney in the mouse [32], we also applied the 4th animal model using rats fed with hydroxy-L-proline (HLP) for 8 weeks to induce CaOx crystal deposition, since early studies indicated that this rat model has little acute renal injury and more closely mimicks the renal CaOx crystal deposition occurring in human kidney stone formers [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“… 4 It has previously been performed to analyze the serum and urine of animal models with CaOx stones, by which potential biomarkers and disturbed metabolic pathways in rats with stones were identified. 15 Recently, metabolomics studies using the urine of patients with kidney stones have also been published, 5 , 6 which are of great significance for the prevention and treatment of kidney stones. However, the previous researches only focused on adults, ignoring children and adolescents.…”
Section: Discussionmentioning
confidence: 99%